2021
DOI: 10.2186/jpr.jpr_d_20_00169
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of intraoral digital impression of inlay preparation according to tooth location and cavity type

Abstract: Purpose: This study aimed to evaluate the influence of tooth location and inlay cavity type on the accuracy of intraoral digital impressions. Methods: Class II inlay preparation was performed on anatomical models of the maxillary first molar (16) and mandibular first molar (46). Mesioocclusal and disto-occlusal cavities were prepared, such that the axial wall of the proximal box measured 1 mm or 2 mm in height. Thus, four types of inlay cavities were prepared in 16 and 46, respectively. Ten digital impressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 28 publications
4
50
1
Order By: Relevance
“…9 However, that study was concerned with the taper between opposing walls, while the present study was concerned with preparation depth. This was also not in agreement with a study by Kim et al, 41 who concluded that cavity width affects both trueness and precision of intraoral scans. In another study by Son et al, 42 they concluded that an increase in the distance between the inlay cavity and adjacent teeth had a favorable effect on precision and trueness of intraoral scans.…”
Section: Discussioncontrasting
confidence: 90%
“…9 However, that study was concerned with the taper between opposing walls, while the present study was concerned with preparation depth. This was also not in agreement with a study by Kim et al, 41 who concluded that cavity width affects both trueness and precision of intraoral scans. In another study by Son et al, 42 they concluded that an increase in the distance between the inlay cavity and adjacent teeth had a favorable effect on precision and trueness of intraoral scans.…”
Section: Discussioncontrasting
confidence: 90%
“…Today, IOS systems have the advantages of ease of use, ergonomic handling, quick scanning, and reliability. Several studies have confirmed the accuracy of IOS systems for multiple applications 1–8 . However, despite the abundance of studies on the accuracy of IOS systems, there is considerable disparity in their designs 9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…The variations can be related to the scanning span, the number of units, scanned substrate material and design, and the condition of the scanned teeth 10 . One of the features that have not been fully investigated is the implication of tooth preparation type on the accuracy of IOS 1–3,9,13–15 . Variations in preparation types and designs, such as crown, onlay, and inlay, may interfere with the scanning process and the capturing of the preparation surface details 16–21 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a laboratory scanner to obtain the reference scans is a limitation. However, the accuracy of the applied laboratory scanner is high, and the application of laboratory scanners to obtain reference datasets has been recommended [ 38 , 39 , 40 , 41 ]. Future studies should be performed by using an industrial grade scanner for high-accuracy reference scans.…”
Section: Discussionmentioning
confidence: 99%